Production, Purification and Characterization of -Lactamase from Clinical Isolate of Acinetobacter baumannii A7 - Afrah Jabbar Lazim; Essam Fadel Alwan Al-Jumaili2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
nn